PENGARUH MEDIA TANAM TERHADAP RESPON FISIOLOGI AKLIMATISASI ANGGREK Cattleya - V. Andriani; I. A.K. Pramushinta (FMIPA : Universitas PGRI Adi Buana, 2017)
Cattleya included in the family Orchidaceae that can be grown using tissue culture methods. Adjustments to the climate into a new environment, known as acclimatization is an important issue when cultivating the plant seedlings are propagated by tissue culture techniques. This study aims to determine the acclimatization media (wood charcoal, husk charcoal, moss and cocopeat ) suitable for a physiological response (weight of the plant and chlorophyll content) Cattleya tissue culture results. Measurement of chlorophyll content using a spectrophotometer. Results obtained in the form of quantitative. Data analysis using ANAVA with SPSS 16 Software. Results showed that rice husk media has a great influence over the weight and chlorophyll content acclimatization Cattleya. Keywords: Cattleya, Acclimatization, Media